Religious People Beetwen Fashion Androgini and Nonbinary Gender - Tressa Risdianti; Ahmad Jamin; Albertos Damni (LPPM IAIN Kudus, 2023)
Androgynous fashion trends incorporate men’s and women’s clothing elements and are often embraced by individuals who challenge traditional gender norms. This research project aims to explore the reactions of religious individuals to non-binary people wearing androgynous clothing in everyday life. Using a narrative inquiry approach, this research collects interview data to analyze critical issues from the informants’ points of view. Informants were selected through an Outcome-based sampling method from Muslim-majority communities and Islamic college. Examining the responses of community members and students is essential to understand their attitudes toward critical issues better. Research analysis involves two distinct stages. First, it is essential to identify patterns in the data obtained from the two groups of informants based on the derived themes. Second, these patterns must be thoroughly compared with theoretical perspectives to ensure that comprehensive and holistic data is produced. Research indicates that religious individuals and students often share different perspectives regarding non-binary individuals who opt for an androgynous appearance.